Health in environment: reduce surgical site infections by applying Florence nightingale’s environmental theory - Anna Rana (Journal of the Pakistan Medical Association, 2020)
Abstract Surgical site infection is one of the most common causes of readmission in hospitals and it also leads to an overall increased burden. This can be decreased by applying basic concepts of Nightingale (1860) “Environmental Theory” while giving care to the patients. Keeping in view Nightingale’s environmental theory, this paper aims to discuss the case of a patient suffering from a surgical site infection. It will help readers to understand the environmental factors which affect the patients’ health and provide a way to promote healing and fast recovery by modifying their environment. Keywords: Florence Nightingale, Environmental Theory, surgical site infection. Continuous...